Pengaruh Kecerdasan Emosional Siwa MTsN 1 Kota Ternate Terhadap Prestasi Akademik - Adiyana Adam; Usman Ilyas (IAIN Ternate, 2022)
The current process towards the goals of education in Indonesia is stillrunning unbalanced because in reality education currently only focuses on one cognitive aspect, namely IQ (intelligent Quotion). Even though IQ is not the only factor that greatly influences student achievement. In the learning process there is a change in the abilities possessed by students in various fields, and that ability is obtained because of the learning effort. Children who master their emotions become more confident, optimistic, have passion and ideals, have the ability to adapt and at the same time they will perform better in school who are able to understand, as well as master the problems that exist Based on the results of research conducted on 50 students MTsN Ternate City shows that the emotional intelligence of students is generally at a value of 34-63% with high emotional intelligence qualifications. This is also in line with the number of students as many as 25 students have an emotional intelligence interval of 50-63%, in the high category, 19 students have an emotional intelligence interval between 35-49% in the medium category and 6 people have an emotional intelligence interval between 10-34 % with low category.